2011
DOI: 10.1177/0333102411405226
|View full text |Cite
|
Sign up to set email alerts
|

Spinal manipulations for the treatment of migraine: A systematic review of randomized clinical trials

Abstract: Current evidence does not support the use of spinal manipulations for the treatment for migraine headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…127 Also concurring with the present analysis, the meta-analysis by Deare et al 126 concluded that acupuncture was not an effective therapy for pain or function in individuals with Fibromyalgia. In their systematic review, Posadzki and Ernst 128 found little data supporting the use of spinal manipulation for headaches. Supporting our conclusions is a recent comprehensive meta-analysis of trials studying glucosamine for osteoarthritis, 132 which found considerable variability in results across trials and concluded that neither glucosamine sulfate or HCl provide pain relief.…”
Section: Safetymentioning
confidence: 99%
“…127 Also concurring with the present analysis, the meta-analysis by Deare et al 126 concluded that acupuncture was not an effective therapy for pain or function in individuals with Fibromyalgia. In their systematic review, Posadzki and Ernst 128 found little data supporting the use of spinal manipulation for headaches. Supporting our conclusions is a recent comprehensive meta-analysis of trials studying glucosamine for osteoarthritis, 132 which found considerable variability in results across trials and concluded that neither glucosamine sulfate or HCl provide pain relief.…”
Section: Safetymentioning
confidence: 99%
“…8 In fact, several systematic reviews have investigated the effectiveness of spinal manipulation in the management of tension type, migraine, and cervicogenic headache. The results of the reviews are inconsistent, since the effectiveness of joint manipulation in tension type headache remains inconclusive; 9 current evidence does not support the use of manipulation for migraine, 10 whereas some positive results have been found for cervicogenic headache. 11 In fact, a review of systematic reviews concluded that the findings reported about effectiveness of spinal manipulation for the management of headaches differed considerably.…”
Section: Scientific Evidence For Manual Therapy In Tension Type and Cmentioning
confidence: 99%
“…More high quality research is needed however to assess the efficacy of MT as a treatment for common recurrent headaches. Recent systematic reviews of randomized clinical trials of MT for the prevention of migraine report a number of significant methodological short-comings and the need for more high quality research before any firm conclusions can be made [35, 36]. Recent reviews of MT trials for tension-type headache and cervicogenic headache are cautious in reporting positive outcomes and the strong need for further robust research [3741].…”
Section: Introductionmentioning
confidence: 99%